Pocillopora tuahiniensis: a new species of scleractinian coral (Scleractinia, Pocilloporidae) from French Polynesia - Johnston, Erika C.; Burgess, Scott C. (Zootaxa, 2023)
Pocillopora tuahiniensis sp. nov. is described based on mitochondrial and nuclear genomic data, algal symbiont genetic data, geographic isolation, and its distribution pattern within reefs that is distinct from other sympatric Pocillopora species (Johnston et al. 2022a, b). Mitochondrial and nuclear genomic data reveal that P. tuahiniensis sp. nov. is a unique species, sister to P. verrucosa, and in a clade different from that of P. meandrina (Johnston et al. 2022a). However, the gross in situ colony appearance of P. tuahiniensis sp. nov. cannot easily be differentiated from that of P. verrucosa or P. meandrina at Mo’orea. By sequencing the mtORF region, P. tuahiniensis sp. nov. can be easily distinguished from other Pocillopora species. Pocillopora tuahiniensis sp. nov. has so far been sampled in French Polynesia, Ducie Island, and Rapa Nui (Armstrong et al. 2023; Edmunds et al. 2016; Forsman et al. 2013; Gélin et al. 2017; Mayfield et al. 2015; Oury et al. 2021; Voolstra et al. 2023). On the fore reefs of Mo’orea, P. tuahiniensis sp. nov. is very abundant ≥10 m and is one of the most common Pocillopora species at these depths (Johnston et al. 2022b). It can also be found at a much lower abundance at shallow depths on the fore reef and back reef lagoon. The holotype is deposited at the Smithsonian Institution as USNM-SI 1522390 and the mtORF Genbank accession number is OP418359.